Stillbirth Among Patients With Diabetes in Pregnancy in Ethiopia: Systematic Review and Meta-Analysis - Belay, Demeke Mesfin; Bayih, Wubet Alebachew; Alemu, Abebaw Yeshambel; Ayele, Amare Simegn; Mekonen, Demewoz Kefale; Birhane, Binyam Minuye (Frontiers in Pediatrics, 2021)
Purpose: Maternal diabetes mellitus and the resulting adverse fetal outcomes including stillbirth in low- and middle-income countries (LMICs) are high. Thus, setting specific evidence is pivotal to plan, evaluate, and improve national preventive measures and to achieve international sustainable development goals. Therefore, this systematic review and meta-analysis was the first of its kind to estimate the pooled prevalence of stillbirth and its determinants among diabetic mothers in Ethiopia. Methods: Primary studies were exhaustively searched using PubMed, ScienceDirect, Web of Science, SCOPUS, and Google Scholar databases, and gray literature found in Addis Ababa and Haramaya University online repositories was accessed. Eligible studies were selected and critically appraised for quality using the Joanna Briggs Institute (JBI) quality appraisal checklist. The overall prevalence of stillbirth among diabetic mothers was estimated using a weighted inverse random-effect model. I2 statistic was used for evidence of heterogeneity. Egger's test and funnel plot were used to check the presence of publication bias. Results: The pooled prevalence of stillbirth among diabetic mothers was 2.39 [95% confidence interval (CI): −0.20, 4.97]. Being a housewife [adjusted odds ratio (AOR) = 2.25; 95% CI: 1.26, 3.23], maternal age of <30 years [AOR = 2.08 (95% CI: 1.02, 3.13)], and gestational age of <37 completed weeks [AOR = 9.76 (95% CI: 7.83, 11.70)] increased the risk of stillbirth among diabetic mothers. Conclusions: The national pooled prevalence of stillbirth among diabetic mothers was 2.39%. Maternal age of <30 years, gestational age of <37 completed weeks, and being a housewife were significantly associated with stillbirth. Trial registration: PROSPERO 2020: CRD4202016774.